Association of 11β-Hydroxysteroid Dehydrogenase Type 1 Expression and Activity with Estrogen Receptor β in Adipose Tissue from Postmenopausal Women - McInnes, Kerry J (2012)
OBJECTIVE: 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1) regenerates active cortisol from inert cortisone in adipose tissue. Elevated adipose tissue 11βHSD1 activity is observed in obese humans and rodents where it is linked to obesity and its metabolic consequences. Menopause is also associated with increased abdominal fat accumulation suggesting that estrogen is also important in adipose tissue metabolism. The purpose of this current study was to establish whether estrogen signalling through estrogen receptors-α and -β (ERα and ERβ) can influence 11βHSD1 in premenopausal and postmenopausal adipose tissue. METHODS: 19 premenopausal (aged 26±5, BMI 23.6±1.6) and 23 postmenopausal healthy women (aged 63±4, BMI 23.4±1.9) were studied. Subcutaneous adipose tissue biopsies and fasting venous blood samples were taken. Body composition was measured by bio-electrical impedance analysis. Human SGBS adipocyte cells were treated with ERα and ERβ-specific agonists for 24h. Basic anthropometric data, Serum 17β-estradiol and progesterone concentrations, ERα and ERβ mRNA levels and 11βHSD1 mRNA, protein and activity levels were assessed. RESULTS: ERβ and 11βHSD1, but not ERα mRNA was significantly increased in adipose tissue from postmenopausal women compared to premenopausal women. ERβ had a significant positive correlation with the mRNA level of 11βHSD1 in adipose tissue from pre- and postmenopausal women. This association between ERβ and 11βHSD1 was greatest in adipose tissue from postmenopausal women. In human SGBS adipocytes, diarylpropiolnitrile (DPN), a selective ERβ agonist increased 11βHSD1 mRNA, protein and activity levels. CONCLUSIONS: We conclude that in adipose tissue, ERβ-mediated estrogen-signalling can upregulate 11βHSD1 and that this may be of particular importance in postmenopausal women.